The Global Resort to Antidumping, Safeguards, and other Trade Remedies amidst the Economic Crisis - Bown, Chad P. (2012)
This paper examines newly available data from the World Bank-sponsored Global Antidumping Database tracking the worldwide use of trade remedies such as antidumping, countervailing duties, global safeguards and China-specific safeguards during the current economic crisis. The data indicate a marked increase in WTO members combined resort to these instruments beginning in 2008 that continued into the first quarter 2009. The use of these import-restricting instruments is increasingly affecting "South-South" trade, i.e., developing country importers initiating and imposing new protectionist measures primarily affecting developing country exporters, with a special emphasis on exports from China. However, the collective value of imports in 2007 for the major (G-20) economies that has subsequently come under attack by the use of import-restricting trade remedies during the period of 2008 to early 2009 is likely less than $29 billion, or less than 0.45 per cent of these economies total imports, though there is substantial variation across countries. While the level of trade affected thus far may be small for most of these economies, a first assessment of some of the case-level data identifies a number of ways in which the crisis use of these import-restricting trade remedies may have economically important welfare-distorting effects on economic activity.